BaltPLA 2 : A new phospholipase A 2 from Bothrops alternatus snake venom with antiplatelet aggregation activity - Dias, Edigar Henrique Vaz; Paschoal, Tamires dos Santos; da Silva, Alisson Pereira; Pereira, DéborahFernanda da Cunha; Simamoto, Bruna Barbosa de Sousa; Matias, Mariana Santos; Santiago, Fernanda Maria; Rosa, José Cesar; Soares, Andreimar; Santos-Filho, Norival A. [UNESP]; Oliveira, Fábio de; Mamede, Carla Cristine Neves (Bentham Science Publishers, 2018)
Background: In last decades, snake venoms have aroused great interest of the medicine due to the pathophysiological effects caused by their toxins. These include the phospholipases A 2 , low molecular weight proteins capable of causing haemorrhagic, myotoxic, inflammatory and neu-rotoxic effects after an ophidian accident. The present work describes the isolation and biochemical characterization of a new PLA 2 isolated from the B. alternatus snake venom, which was named BaltPLA 2 . Method: The rapid and efficient purification of this toxin was performed using only two chromatography steps (anion exchange and hydrophobic chromatography). Results: BaltPLA 2 is an acidic protein (pI 4.4) with an apparent molecular mass of 17000 (SDS-PAGE) and 14074.74 Da (MALDI TOF/TOF). Analysis of fragments ion by MS / MS showed the following internal amino acid sequence SGVIICGEGTPCEK, which did not exhibit homology with other PLA 2 from the same venom. BaltPLA 2 is a catalytically active, which displayed an anticoagulant action, inhibition of platelet aggregation induced by epinephrine (~ 80%) and ADP (24%). BaltPLA 2 also was able to induce myonecrosis and the release of cytokines (IL-10, IL-12 and TNF-α) in macrophages culture. Conclusion: The results presented in this work greatly contribute to a better understanding of the mechanism of enzymatic and pharmacological actions of PLA 2 s from snake venoms and they may contribute to its application in medical research.
Keywords: Bothrops alternatus; Inflammation; Myonecrosis; Phospholipases A 2; Platelet aggregation; Snake venom